Analisis Perilaku Wisawatan Terhadap Lingkungan di Lokasi Wisata dalam Wilayah Kota Kupang Berbasis Theory of Planned Behavior - Deddy Barnabas Lasfeto; Yohan A. A. Lada; Tuti Setyorini (Jurnal Inovasi Kebijakan, 2022)
This study discusses the impact of external factors at tourist sites on tourist environmental behaviour. The tourists in this study were students in Kupang City. The multiple-group analysis function was used to make comparisons of the education levels of student tourists at tourist spots to test the moderating effect of education levels. Through analysis of survey data collected from tourists at several tourist sites in the city of Kupang, it is recommended to encourage the formation of good communities in supporting environmentally responsible behaviour in tourist attractions. This finding also confirms that education level moderates the relationship between tourist intentions and actual environmentally responsible behaviour.